In vitro evaluation of antimicrobial activity of sealers and pastes used in endodontics - Leonardo, Mário Roberto [UNESP]; Da Silva, Léa Assed Bezerra; Tanomaru Filho, Mario [UNESP]; Bonifácio, Kleber Cortês [UNESP]; Ito, Izabel Yoko (Wolters Kluwer, 2000)
The antimicrobial activity of four root canal sealers (AH Plus, Sealapex, Ketac Endo, and Fill Canal), two calcium hydroxide pastes (Calen and Calasept), and a zinc oxide paste was evaluated. Seven bacterial strains were used, six of them standard; Micrococcus luteus ATCC 9341, Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Staphylococcus epidermidis ATCC 12228, Escherichia coli ATCC 25922, and Enterococcus faecalis ATCC 10541. There was a wild strain of Streptococcus mutans isolated from saliva obtained in an adult dental clinic. Activity was evaluated using the agar diffusion method with Brain Heart Infusion agar and Müller Hinton medium seeded by pour plate. Calcium hydroxide-based sealers and pastes were either placed directly into 4.0 × 4.0 mm wells or by using absorbent paper points. The plates were kept at room temperature for 2 hr for diffusion. After incubation at 37°C for 24 hr, the medium was optimized with 0.05 g% TTC gel and inhibition haloes were measured. All bacterial strains were inhibited by all materials using the well method. However, when the materials were applied with absorbent paper points, Enterococcus faecalis was not inhibited by zinc oxide, and Pseudomonas aeruginosa was not inhibited by AH Plus, Fill Canal, and the zinc oxide-based paste. We conclude that sealers and pastes presented antimicrobial activity in vitro and culture medium optimization with 0.05 g% TTC gel facilitated observation of the inhibition haloes. Copyright © 2000 by The American Association of Endodontists.